2015
DOI: 10.1111/cts.12304
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models of Barrett's Esophagus and Esophageal Adenocarcinoma–Past, Present, and Future

Abstract: Esophageal adenocarcinoma is the fastest rising cancer in the United States. It develops from long-standing gastroesophageal reflux disease which affects >20% of the general population. It carries a very poor prognosis with five-year survival <20%. The disease is known to sequentially progress from reflux esophagitis to a metaplastic precursor, Barrett's esophagus and then onto dysplasia and esophageal adenocarcinoma. However, only few patients with reflux develop Barrett's esophagus and only a minority of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 62 publications
(99 reference statements)
0
42
1
Order By: Relevance
“…These aspects have negatively affected the performance of long‐term longitudinal studies and limited the recruitment of large human cohorts, as demonstrated by the limited number of enrolled subjects in various studies (Tables 1–3). Second, the interactions within the esophageal environment are difficult to reproduce in vitro , which limits the possibility of studying the esophageal ecosystem using in vitro models, while the available animal models to study esophageal diseases (e.g., the BE animal model based on a surgical anastomosis in the rat) are complex and have several shortcomings, including species differences, the requirement of surgical expertise, duration, and costs . Third, culture‐dependent methods can contribute only partially to depicting the population structure of the resident microbiota, since several taxa are difficult or impossible to cultivate.…”
Section: Discussionmentioning
confidence: 99%
“…These aspects have negatively affected the performance of long‐term longitudinal studies and limited the recruitment of large human cohorts, as demonstrated by the limited number of enrolled subjects in various studies (Tables 1–3). Second, the interactions within the esophageal environment are difficult to reproduce in vitro , which limits the possibility of studying the esophageal ecosystem using in vitro models, while the available animal models to study esophageal diseases (e.g., the BE animal model based on a surgical anastomosis in the rat) are complex and have several shortcomings, including species differences, the requirement of surgical expertise, duration, and costs . Third, culture‐dependent methods can contribute only partially to depicting the population structure of the resident microbiota, since several taxa are difficult or impossible to cultivate.…”
Section: Discussionmentioning
confidence: 99%
“…37 In pigs, the esophageal and gastroesophageal junctional anatomy and physiology are comparable with that of human beings, both sharing the existence of large, dissectible submucosal glands, making the pig a preferred model for analogous clinical applications. 11,24,38 In particular, pigs are used commonly to test new surgical and endoscopic techniques in the esophagus. Recently, a pig model of esophageal injury and repair was developed in which endoscopic radiofrequency ablation was used to induce injury, followed by the study of cellular biology of the repair process, including the location and role of proliferative cells.…”
Section: Examples Of Large Animal Models In Digestive Diseasementioning
confidence: 99%
“…Of the two cases reported in dogs, one also progressed to EAC . Despite both the dog and baboon developing BE spontaneously, they failed to become popular as preclinical models because they are resource intensive and can take up to 30 months to develop BE and 60 months to develop EAC …”
Section: In Vivo Modelsmentioning
confidence: 99%